The Urgency of Digital Competence in Encouraging Innovative Teaching in the Classroom for Enhancing Education Quality - Ragil Wahyuda Abrar; Syawaluddin Ritonga; Zulfadli Nasution; Amin Harahap (Lembaga Riset Mutiara Akbar, 2025)
In today's world where technology is changing everything, knowing how to use digital tools is very important for making classroom learning better. This article talks about why it is important for teachers to learn digital skills. This will help them come up with new ways to teach that fit what students need in the 21st century. This research uses a qualitative approach by looking at books and articles to collect information from different sources. The research shows that when teachers know how to use digital tools, they can use technology in creative ways in their lessons. This makes learning more interactive, personalized, and focused on the student. By using different digital tools and platforms, teachers can teach more effectively and give students access to learning materials from all over the world. Helping teachers get better at using digital tools should be part of a larger plan to make education better. This study shows that teachers who are good with technology are very important for creating new, effective, and lasting ways of learning.